2015
DOI: 10.1136/vr.102724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between echocardiographic and non‐ECG‐gated CT measurements in dogs

Abstract: The aim of this study was to compare echocardiographic measurements with non-ECG-gated contrast-enhanced cardiac CT measurements in dogs. Fifty-seven dogs were included in the study. The following echocardiographic parameters were measured: M-mode interventricular septum in diastole and systole, left ventricular internal diameter in diastole and systole, left ventricular free wall in diastole and systole, 2D left atrial maximal diameter, 2D left atrium to aorta ratio in diastole, 2D aortic annulus in systole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…When acquired in diastole, this results in improved cardiac image quality . However, electrocardiographic‐gating is not widely available in veterinary practice . Imaging the cardiac structures with CT angiography, but without electrocardiographic gating, is often challenging due to motion artifact.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…When acquired in diastole, this results in improved cardiac image quality . However, electrocardiographic‐gating is not widely available in veterinary practice . Imaging the cardiac structures with CT angiography, but without electrocardiographic gating, is often challenging due to motion artifact.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that echocardiographic and non‐electrocardiographic‐gated CT angiography measurements of the aortic valve annulus were moderately correlated and correlated better than all other measured parameters. This was thought to be due to decreased motion of the aorta during systole and diastole, relative to the other cardiac structures . The decreased motion of the aorta may also mean that the coronary ostia that arise from the aorta exhibit decreased motion throughout the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data demonstrate that timing during the cardiac cycle need not be a critical consideration. However, high motion anatomy like the pulmonary valve leaflets can introduce difficulty when measuring landmarks leading to inaccurate measurements if gating is not employed . A lack of ECG‐gating can be overcome with a high‐pitch technique using a dual‐source scanner; however, the scanners with dual‐source technology are commonly cost prohibitive in clinical veterinary medicine .…”
Section: Discussionmentioning
confidence: 99%